Application of Dmaic and Business Intelligence for analysis and standardization of the Andon System in a vehicle manufacturer - Oliveira, Eduardo de Freitas; Fonseca Júnior, Lázaro Antônio da; Santos, Aline Gonçalves dos; Nunes, Deivid Marques (Brazilian Journal of Production Engineering, 2026)
In a manufacturing environment, the Andon system plays a crucial role in the immediate signaling of problems that occur on the production line and is fundamental for driving corrective and preventive actions for the identified issues. In this context, the present article aims to apply the DMAIC methodology to improve the management of occurrences recorded by the Andon System in an automotive assembly plant. To achieve this, analyses of system data were conducted, along with a brainstorming session involving multifunctional teams from different areas to understand the main reasons for system activation, the measurement of these data, and the proposal of a new management system. As a result, it was possible to identify that the main problems were caused by the lack of standardization of occurrences, insufficient data in the records for analysis and decision-making, lack of periodic evaluations, and lack of training. Consequently, the occurrence-handling actions were standardized, eliminating obsolete and inaccurate data to generate precise and real-time information through the application of Business Intelligence. The activation occurrences are now stored in a unified environment with clearer visualization of records, facilitating and enabling more assertive decision-making in action plans with preventive and corrective measures.
Keywords: DMAIC; Six Sigma; Andon System; Business Intelligence